Dermatophytes Fungi Trichophyton Verrucosum A Causative Agent of Ringworm Disease on Cattle - Gholib, Djaenudin; Rachmawati, S (Indonesian Bulletin of Animal and Veterinary Sciences, 2010)
Ringworm is a superficial mycosis which affected surface parts of the body such as skin, hair, nail or horn. These parts are rich of keratine that required for the fungi to grow. The disease affects both animals and human (zoonosis), and it results in hair loss, crusted of skin, swelling, erythema and itchy. The disease is considered as important because it affects health condition and animal production. The causative agent is fungal dermatophytes group especially Trichophyton verrucosum. Cases occurred in Indonesia and first officially reported and published in 1980 on imported dairy cows from Australia, and a causative agent was identified as Trichophyton verrucosum. Recently, the same cases occurred in young dairy calves and lactating cattle. Pathogenity test in rabbits by artificial infection revealed the growth of the colonies. Post infection and vaccination provide resistency on cattle. Therefore beside therapeutic method, the vaccination program is useful to be included in prevention of the disease. Key words: Trichophyton verrucosum, ringworm, cattle